ANALISIS INOVASI DENGAN METODE BUSINESS MODEL CANVAS DAN TEN TYPES OF INOVATION PADA LAZISMU UNIVERSITAS MUHAMMADIYAH GRESIK UNTUK MENINGKATKAN PENDAPATAN - Lintang Trias Kurnia Putri; Dwi Komara, Beni (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Fundraising or fundraising is important so that civil society organizations can take part in a sustainable manner. Fundraising Lazismu UMG has grown rapidly, currently it has been able to help more than 200 mustahik. Lazismu UMG continues to be determined to make various innovations so that it can help more people in need. This study aims to determine industry analysis, fundraising competitors and the internal conditions of Lazismu Muhammadiyah Gresik University from the perspective of the Ten Types of Innovation method. Furthermore, to find out what innovative tactics can be chosen so that Lazismu Universitas Muhammadiyah Gresik can increase donation revenue. Research data obtained through interviews, observation and documentation. Interview 1 leader of Lazismu UMG, 3 volunteer members, and 2 competing zakat institutions. Based on the implementation of the research, the results of the analysis of the Business Model Canvas Lazismu UMG were obtained. From this research it was also found that Lazismu UMG data had implemented 3 tactics of the Ten Types of Innovation namely Collaboration, Simplification Experience and Superior Product. In addition, this study found two new tactics that are suitable for use by Lazismu UMG, namely Brand Extension and Personalized Service